Analyzing factors influencing dairy farmers’ intention to implement animal welfare practices: a case study of Germany - Grotsch, Henrike; Mergenthaler, Marcus; Schulze, Holger (Frontiers in Animal Science, 2025)
In context of the growing focus on animal welfare in dairy farming, this study explores the behavioral intention to implement animal welfare (AW) practices among dairy farmers in Germany. Within this investigation, AW practices are defined as targeted practices to enhance dairy cows’ well-being. A quantitative survey of 682 farmers was conducted. The results of a regression analysis revealed that striving for continuous enhancement, along with intrinsic motivation, significantly drives the intention to implement AW practices. Additional efforts and costs do not influence dairy farmers’ intention. A collective, sector-wide effort is essential to ensure that farmers have the necessary freedom to navigate respective changes by providing the necessary structural backing to sustain meaningful improvements in animal welfare.